Issues of Corrective Action of Future Teachers - Xatamovna, Meliboyeva Nodira (European Journal of Life Safety and Stability (2660-9630), 2021)
The article provides information about the correctional work of future teachers. When talking about the correction of the activities of future teachers is understood to improve their pedagogical skills, improve, develop more on their own, improve knowledge.